2016
DOI: 10.1080/13854046.2016.1238510
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent analysis of a digital Trail Making Test

Abstract: Objective The purpose of the current study was to use a newly developed digital tablet-based variant of the TMT to isolate component cognitive processes underlying TMT performance. Method Similar to the paper-based trail making test, this digital variant consists of two conditions, Part A and Part B. However, this digital version automatically collects additional data to create component subtest scores to isolate cognitive abilities. Specifically, in addition to the total time to completion and number of err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 38 publications
12
87
0
1
Order By: Relevance
“…The UX-TMT showed significant correlations with the MMSE-J ( r = .77) and the trail making test part B of the MoCA-J ( r = .56). Fellows et al reported that the digital trail making test (dTMT) showed significant correlation with paper version of trail making test part A ( r s = .541) and part B ( r s = .799), respectively, in 68 participants comprised of the elderly controls and patients including PD and MCI [ 26 ]. They administrated the test by using a stylus instead of pencil and used 26 encircled numbers and letters in paper version and 20 or 19 encircled numbers and letters in tablet version TMT, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The UX-TMT showed significant correlations with the MMSE-J ( r = .77) and the trail making test part B of the MoCA-J ( r = .56). Fellows et al reported that the digital trail making test (dTMT) showed significant correlation with paper version of trail making test part A ( r s = .541) and part B ( r s = .799), respectively, in 68 participants comprised of the elderly controls and patients including PD and MCI [ 26 ]. They administrated the test by using a stylus instead of pencil and used 26 encircled numbers and letters in paper version and 20 or 19 encircled numbers and letters in tablet version TMT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the next generation applications take advantage of touch sensors and mobile technology [ 25 , 30 ]. They have been applied to exploring behavioral indices and quantitative measurements of perturbed cognitive processes [ 25 , 26 , 30 , 47 ]. Other possibility includes real-time and remote behavioral monitoring of cognitive and motor function in the elderly [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive flexibility and divided attention were assessed with the Trail Making Test (TMT) [ 37 ]. It requires speed and good visual scanning skills, as well as inhibitory control and visual/spatial sequencing [ 36 , 38 ]. In condition A, participants are instructed to draw lines between numbers as fast as possible (1-2-3-4-…), while in condition B, the instruction is to draw lines between numbers and letters and switch between those (1-A-2-B-3-C-…).…”
Section: Methodsmentioning
confidence: 99%
“…Other authors calculate derived scores based on the B/A ratio and the B-A difference, arguing that the switch cost between the primary scores reflect "the additional cognitive control required to switch between sequencial numbers and letters" (Arbuthnott & Frank, 2000, p. 519). However, this type of score is "best conceptualized as reflecting a combination of several cognitive functions" (Kortte et al, 2002), which complicates the identification and isolation of specific executive functions (see also Fellows et al, 2017). Naturally, both the primary and the derived scores are valid measurements in the TMT, and the choice of one or another may be driven by the particular needs of each study.…”
Section: Background Of the Studymentioning
confidence: 99%